Pengaruh Media Motion Video Education Kelas Ibu Hamil terhadap Peningkatan Pengetahuan dan Sikap Ibu Hamil tentang Anemia - Vivi; Antono Surjoputro; Syamsulhuda Budi Musthofa (Syntax Corporation, 2023)
Background: Classes for pregnant women, are a means to learn together about health for pregnant women, in the form of face-to-face groups that aim to increase the knowledge and skills of mothers regarding pregnancy, pregnancy care, childbirth, postpartum care, newborn care, myths, infectious diseases and birth certificates. Pregnant women need interesting educational tools to increase their knowledge and attitudes about anemia. The use of Educational Motion Video Media aims to increase the knowledge and attitudes of Pregnant Women about anemia. Method: Article review is made using the literature review method. The articles used were obtained from relevant articles in the last 10 years. Results: From several studies that have been conducted, the results obtained. The use of Motion Video Education Media can increase the knowledge and attitudes of pregnant women about anemia. Conclusion: Media Motion Video Education is very useful for increasing the knowledge and attitudes of pregnant women about anemia.